How long does it take to discover a species?. Issue 8 (16th November 2020) - Goodwin, Zoë A.; Muñoz-Rodríguez, Pablo; Harris, David J.; Wells, Tom; Wood, John R. I.; Filer, Denis; Scotland, Robert W.
Abstract : The description of a new species is a key step in cataloguing the World's flora. However, this is only a preliminary stage in a long process of understanding what that species represents. We investigated how long the species discovery process takes by focusing on three key stages: 1, the collection of the first specimen; 2, the publication of the species name; and 3, the date when a minimum number of 15 accurately named specimens are available. We quantified the time lags associated with these stages for several groups of plants with different numbers of species and from different regions, including the 20 most species-rich Angiosperm families. Our analyses reveal that it takes decades to accumulate a minimum number of specimens to allow subsequent studies of any kind. The time lag between stages 1 and 3 is consistently over 70 years with groups such as the tropical genus Aframomum reflecting an average time lag of over 100 years. In light of our results, we suggest that species discovery is most accurately characterized as a lengthy process of knowledge accumulation, often spanning decades, rather than a one-off event.